As competências socioemocionais na educação básica: a Revista Nova Escola em pauta - Páscoa, Emanuela Galvão (Universidade do Vale do Rio dos Sinos, 2021)
This dissertation analyzes how socio-emotional skills enter basic education, in the contemporary, through an analysis of reports from the Revista Nova Escola. The research carried out was of a qualitative nature and was based on Cultural Studies from the point of view of hypercritique, with the aim of problematizing and analyzing the Revista's reports, in the 2018/2019-time frame. To develop this research, the following investigative question was taken: How does the Revista Nova Escola address socio-emotional Skills in Basic Education in Contemporary? To seek to answer it, we base ourselves on studies on contemporary teaching, skills, socio-emotional skills, learning and teacher training. In the analysis of 16 reports from the Revista Nova Escola, both the narratives and the images were used to produce meanings about the socio-emotional skills that circulate in these reports. Legal documents, such as the Common National Curriculum Base (BRAZIL, 2017) and the Law of Guidelines and Bases (BRAZIL, 1996), were used to contextualize and enhance the analyses. It was also observed the relationship of socio-emotional skills with what Revista Nova Escola selects as pedagogical truths of that time, in a structural duality, which divides the curriculum into knowledge that serves the social strata according to what each one represents for the society and for the neoliberal economy. As a result, it was found that socio-emotional competences are products manufactured by neoliberal logic through NGOs, institutes and large companies, which promise, when entering public policies, to assist and/or subsidize training so that teachers align with the perspective of work with socio-emotional skills and, consequently, conduct the conduct of education professionals and students in basic education, leading them to assume a life and education with neoliberal precepts.
Keywords: Competências socioemocionais; Emoções; Docência; Formação integral; Aprendizagem; Educação básica; Socioemotional skills; Emotions; Teaching; Comprehensive training; Learning; Basic education; ACCNPQ::Ciências Humanas::Educação